Universal Neutral-Atom Quantum Computer with Individual Optical Addressing and Nondestructive Readout - A.G. Radnaev; W.C. Chung; D.C. Cole; D. Mason; T.G. Ballance; M.J. Bedalov; D.A. Belknap; M.R. Berman; M. Blakely; I.L. Bloomfield; P.D. Buttler; C. Campbell; et al. (PRX Quantum)
Quantum computers must achieve large-scale fault-tolerant operation to deliver on their promise of transformational processing power. This will require thousands or millions of high-fidelity quantum gates and similar numbers of qubits. Demonstrations using neutral-atom qubits trapped and manipulated by lasers have shown that this modality can provide high two-qubit gate (cz) fidelities and scalable operation. However, the gates in these demonstrations are driven by lasers that do not resolve individual qubits, with universal computation enabled by physical midcircuit shuttling of the qubits. This relatively slow operation may greatly extend run times for useful large-scale computation. Here, we demonstrate a universal neutral-atom quantum computer with gate rates limited by optical switching times, rather than shuttling, by individually addressing tightly focused laser beams at an array of single atoms. We achieve cz fidelity of 99.35(4)% and local single-qubit R_{Z} gate fidelity of 99.902(8)%  in both cases accounting for leakage out of the computational basis. Moreover, we demonstrate nondestructive readout of alkali-atom qubits with 0.9(3)% loss, which boosts operational speed. This technique also enables us to measure a state-of-the-art cz fidelity of 99.73(3)% when excluding atom-loss events, which may be mitigated through erasure conversion. Our results represent a critical step toward large-scale fault-tolerant neutral-atom quantum computers that can execute computations on practical timescales.